"If I could burn the space": on homelessness and the collapse of subjectivity in S.Y. Agnon's A Guest for the Night*. Issue 1 (2nd January 2019) - Ophir, Riki
ABSTRACT: A Guest for the Night, one of Agnon's greatest novels, has long been considered to have dealt with the demise of Jewish Eastern Europe, Zionism and the art of the novel. This article offers a different reading, showing Agnon's novel as a radical work that may have greatly exceeded its author's intentions. Focusing on the irony directed at the novel's narrator, I claim that A Guest for the Night calls on its readers to reconsider common premises regarding the history and politics of Eretz Israel/Palestine.